Experiences in Sensor-Augmented Pump Therapy in Families with two Children with Type 1 diabetes: A Qualitative Study - Bomba, Franziska; Müller-Godeffroy, Esther; von Sengbusch, Simone (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Caring for a child with type 1 diabetes is a tremendous challenge for a family. The aim of the study was to explore the experiences of transition to sensor-augmented pump therapy (SAP) in families with 2 affected children and the internal and external conditions which potentially impede or facilitate the adjustment process.Methods 5 families (9 parents, 8 children and adolescents) who used the SAP technology for 6 months were interviewed to describe their experiences. The interviews were analysed using thematic content analysis.Results Qualitative analysis of the transcribed interviews revealed that the adaptation process to SAP consisted of several phases and differed among families. There were benefits as well as hassles of using SAP with regard to managing the diabetes, and psychosocial issues: school and peer relations, as well as family relations. While parents clearly regarded the improved metabolic control and hypoglycaemic safety as the most important benefits of SAP, the hassles reported as most important covered a wide range, from technical problems of the system to family conflicts. On the whole, families rated the experience of using SAP as a positive one, with most recommending SAP to other families as long as they were willing to come to terms with the technology and commit to the work and time involved.Conclusion Sensor-augmented pump therapy can be extremely beneficial and a resource for families who care for more than one child with diabetes. During the adaptation process there is a great need of education and frequent follow-up e. g., by telemedical support.
Keywords: insulin infusion systems; blood glucose self-monitoring; telemedicine; qualitative research